Pengaruh Literasi Keuangan Dan Gaya Hidup Terhadap Perilaku Konsumtif Mahasiswa Program Studi Manajemen S1 Universitas Pamulang (Studi Kasus Mahasiswa Semester 8) - Subali, Subali; Lina Nofiana (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. The purpose of this study was to determine the effect of financial literacy and lifestyle on consumer behavior in financial management students at Pamulang University. The method used was quantitative. The sample used was 100 respondents. Data analysis used validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients and hypothesis tests. The results of this study are that Financial Literacy has no significant effect on Consumer Behavior with a determination coefficient value of 0.1% and the hypothesis test obtained t count < t table or (-0.297 > 1.984). Lifestyle has a significant effect on Consumer Behavior with a determination coefficient value of 77.6% and the hypothesis test obtained t count > t table or (18.447 > 1.984). Financial Literacy and Lifestyle simultaneously have a significant effect on Consumer Behavior with a regression equation Y = 8.800 - 0.017X1 + 0.783X2. The coefficient of determination is 77.6%, while the remaining 22.4% is influenced by other factors. The hypothesis test obtained a calculated F value > F table or (168.438 > 3.160). Keywords: Financial Literacy, Lifestyle, Consumptive Behavior.